Chapter 2 Does the God of Classical Theism Exist? - Koons, Robert C. (Taylor & Francis, 2023)
The God of classical theism can be characterized by four features: uncausedness, atemporality, pure actuality, and the identity of divine essence and existence. A certain long-standing program in natural theology provides good grounds for accepting the existence of such a being. In this chapter, I focus on three arguments from St. Thomas Aquinas: the First and Second Ways (from the Summa Theologiae Part I), and his analysis of essence and existence in De Ente. These arguments provide support for the existence of a First Cause with all four of the characteristics of classical theism. I also argue that we can go on to infer God's personality, intelligence, infinity, and perfection. Finally, there is little doubt that, if the God of classical theism exists, that unique Being must be identified with the God of the Bible.